2022
DOI: 10.3390/v14061308
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of Activin Receptor-like Kinase 5 Interfere with SARS-CoV-2 S-Protein Processing and Spike-Mediated Cell Fusion via Attenuation of Furin Expression

Abstract: Screening of a protein kinase inhibitor library identified SB431542, targeting activin receptor-like kinase 5 (ALK5), as a compound interfering with SARS-CoV-2 replication. Since ALK5 is implicated in transforming growth factor β (TGF-β) signaling and regulation of the cellular endoprotease furin, we pursued this research to clarify the role of this protein kinase for SARS-CoV-2 infection. We show that TGF-β1 induces the expression of furin in a broad spectrum of cells including Huh-7 and Calu-3 that are permi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 99 publications
0
3
0
Order By: Relevance
“…1010,1013,1017 Despite comprehensive cardiovascular monitoring for galunisertib did not detect medically relevant cardiac toxicity in cancer patients, 1018 galunisertib-related uncontrolled cytokine release was reported in patients with advanced solid tumors in a phase 1 trial (NCT01646203). 1019 Other TβRI kinase inhibitors such as SM16, SD-208, NP-40208, SB-431542, LY3200882, LY364947, and vactosertib (EW-7197) also showed therapeutic potential in pre-clinical studies on tumors [1020][1021][1022][1023][1024][1025][1026] as well as many other diseases such as cardiovascular diseases, 565,[1027][1028][1029][1030] renal diseases, 1031 ophthalmic diseases, 1032 skeletal diseases, 1033 fibrotic diseases, [1034][1035][1036] inflammatory diseases, [1037][1038][1039] Chagas disease, 1040,1041 coronavirus disease 2019 (COVID-19), 1042 and wound healing. [1043][1044][1045] Targeting SMADs.…”
Section: Alteration Of Tgf-β Activationmentioning
confidence: 99%
“…1010,1013,1017 Despite comprehensive cardiovascular monitoring for galunisertib did not detect medically relevant cardiac toxicity in cancer patients, 1018 galunisertib-related uncontrolled cytokine release was reported in patients with advanced solid tumors in a phase 1 trial (NCT01646203). 1019 Other TβRI kinase inhibitors such as SM16, SD-208, NP-40208, SB-431542, LY3200882, LY364947, and vactosertib (EW-7197) also showed therapeutic potential in pre-clinical studies on tumors [1020][1021][1022][1023][1024][1025][1026] as well as many other diseases such as cardiovascular diseases, 565,[1027][1028][1029][1030] renal diseases, 1031 ophthalmic diseases, 1032 skeletal diseases, 1033 fibrotic diseases, [1034][1035][1036] inflammatory diseases, [1037][1038][1039] Chagas disease, 1040,1041 coronavirus disease 2019 (COVID-19), 1042 and wound healing. [1043][1044][1045] Targeting SMADs.…”
Section: Alteration Of Tgf-β Activationmentioning
confidence: 99%
“…TGF-β1 has been suggested to play some crucial roles in SARS-CoV-2 infection. Subsequently, the use of some TGF-β1 inhibitors has been proposed to mitigate the current COVID-19 pandemic [ 31 , 256 ].…”
Section: Roles Of Tgf β In Viral Infection At the Non-maternal–fetal ...mentioning
confidence: 99%
“…It is noteworthy that TGF-β1 could induce enhanced expression of cellular receptors for viral entry via the Smad pathway. In recent SARS-CoV-2 research, Mezger and colleagues reported that activation of the Smad pathway via TGF-β1 or ALK5 agonists led to increased expression of furin, a protease that cleaves the spike protein of SARS-CoV-2, in a broad spectrum of cells including Huh-7 (a permanent cell line established from male hepatoma tissue), and Calu-3 cells (epithelial cells isolated from lung tissue derived from a male patient with lung adenocarcinoma), which enhanced susceptibility to SARS-CoV-2 infection in these cells [ 256 ]. Expanding the above findings to further studies to investigate possible mechanisms of transplacental infection of the SARS-CoV-2 is highly recommended.…”
Section: The Smad Pathway and Promising Future Approachesmentioning
confidence: 99%